Pemberian Nilai Tambah Produk Porang - Yanuarizal Ramadhan S.; Nabila Darin Fakhira; Alfian Muhammad Fauzi; Septiyan Nur Rois; Fauzan Abid Ramadhan Wibowo; Akmalia Imbi Febriyanti Hidyarko; Fany A Wellianto; Geofanny Putra Pratama; Eva Wahyu Agustina; Yoga Brilliant Islamay P. (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
The economy of the people of Jeruk village during the Covid 19 pandemic was greatly affected for the people of Jeruk village to continue living costs. Various efforts have been made by the people of Jeruk village to be able to improve their respective economies. Seeing the geographical conditions and soil fertility in Jeruk village, it is very supportive to be planted with various kinds of plants. On the other hand, the Porang plant has recently been widely used and sought after, so that the people of Jeruk village plant a lot of Porang plants which are believed to have many benefits. However, the people of Jeruk village only sell Porang crops, so the selling price is not optimal. With a little processing on the Porang plant, it can increase the selling price of the Porang plant. Educational and discussion activities were chosen because it is hoped that this activity will be the first step in improving the economy of the Jeruk village community. Keywords: Porang, Covid-19, Education